Uso de pornografia e sua influência na satisfação com os relacionamentos amorosos - Baumel, Cynthia Perovano Camargo (2019)
This thesis, developed as 5 separate studies, used different methodological research approaches in order to verify the influence of the use of, and of the attitudes towards pornography in the evaluation of satisfaction within love relationships. Study 1 presents a systematic literature review that sought to identify the definitions of pornography used by researchers and the perceived effects of using such material on love relationships, with a final database of 45 articles. Within the sample studied, sexually explicit material was identified as the most accepted definition of pornography. Study 2 sought to identify and understand the attitudes that men and women have regarding pornography, as well as to verify the perceived advantages and disadvantages of using this type of material in love relationships. Twenty participants, equally distributed regarding gender, with an average age of 25,7 years (SD = 2,06), born in Brazil, were interviewed using a semi-structured script. The results showed that the difference between genders in the approach and in the use of pornography was identified as a significant variable. Study 3 used exploratory and confirmatory factor analyses to validate two of the instruments used in the thesis: the Sexual Satisfaction Index and the Attitudes toward Pornography Scale, built specifically for this research. The instruments analysed showed favourable indicators, demonstrating the adequacy of the proposed models. Studies 4 and 5 sought to describe the use and attitudes towards pornography and characteristics of the participants' love relationship, as well as to present a model that would aid in understanding satisfaction with the love relationship and the contribution of the use and the attitudes towards pornography in this using an online questionnaire. Study 4 had 1382 participants (77,4% women) with an average age of 30,06 years (SD = 9,84). Sexual satisfaction, intimacy and commitment were the significant variables that contributed to the perception of satisfaction with the relationship, to men as well as to women. Regarding the contribution of pornography, the use of and the negative attitude towards pornography contributed significantly to the negative assessment of the satisfaction with the relationship, although the percentage of explanation for these models is small. Study 5 used 200 participants from the previous study who answered the questionnaire as members of a couple. It sought to describe the use of pornography and characteristics of the love relationships of 100 couples in hetero-affective relationships, as well as to present a model that would help understanding the satisfaction with love relationships and the contribution of the use of and the attitudes towards pornography in this evaluation, considering the interdependence of partners in the love dyad. The relationship variables appeared as significant in the evaluation of satisfaction with the relationship. Specifically, the use of pornography by men has emerged as a significant variable that has contributed to the assessment of satisfaction with the love relationship of both men and women – however small the total explanation of the model has shown to be.